2019
DOI: 10.3892/ijmm.2019.4431
|View full text |Cite
|
Sign up to set email alerts
|

miR‑195 promotes LPS‑mediated intestinal epithelial cell apoptosis via targeting SIRT1/eIF2a

Abstract: A microarray analysis of an animal model with experimental sepsis induced by caecal ligation and puncture revealed that the level of microRNA-195 (miR-195) was upregulated. However, to the best of our knowledge, the role of miR-195 in sepsis remains unknown. The present study investigated the effect of miR-195 on apoptosis in sepsis and investigated the underlying mechanism. The level of miR-195 was measured in human intestinal epithelial cells following exposure to lipopolysaccharide (LPS). cell viability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The overexpression of miR-195-5p can inhibit the YAP-mediated Wnt/β-catenin signaling pathway and promote cell apoptosis, so it may be a potential therapeutic target for cancer. Zhao et al 's results [24] revealed that silencing of miR-195 prevented apoptosis and alleviated cell injury in LPS-induced NCM460 cells [25]. In our study, we observed slight (but statistically important) differences between the levels of apoptosis in the WT SkMDS/PCs population vs. SkMDS/PCs treated with miR-195 inhibitor (Figure 4), which were in favor of the "native" wild-type cells.…”
Section: Discussionsupporting
confidence: 48%
“…The overexpression of miR-195-5p can inhibit the YAP-mediated Wnt/β-catenin signaling pathway and promote cell apoptosis, so it may be a potential therapeutic target for cancer. Zhao et al 's results [24] revealed that silencing of miR-195 prevented apoptosis and alleviated cell injury in LPS-induced NCM460 cells [25]. In our study, we observed slight (but statistically important) differences between the levels of apoptosis in the WT SkMDS/PCs population vs. SkMDS/PCs treated with miR-195 inhibitor (Figure 4), which were in favor of the "native" wild-type cells.…”
Section: Discussionsupporting
confidence: 48%
“…Inhibition of HDAC promotes acetylation at speci c lysine residues on histones and other nuclear and cytoplasmic proteins, which in turn modulates pivotal cellular functions such as chromosome remodeling, gene transcription, and cell proliferation 45,46 . It has previously been reported that HDAC inhibitors such as MS-275 25 , MC-1568 26 , Tub-A 24 , EX-527 27,28 , SAHA [29][30][31] , and VPA 23,26,32 can protect intestinal epithelial cells, improve intestinal tight junctions, support intestinal structure and function, and prevent bacterial translocation.…”
Section: Discussionmentioning
confidence: 99%
“…These epithelial cells are sensitive to inflammatory processes and to ROS levels that exceed the total antioxidant capacity [ 30 , 31 ]. LPS-induced injury to the intestinal tissue is also associated with increased apoptosis [ 32 ]. Consistent with our results, sulforaphane has been shown to protect the gastrointestinal mucosa from oxidative injury and inflammation induced by H. pylori and non-steroidal anti-inflammatory drugs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%